2010
DOI: 10.2353/ajpath.2010.100212
|View full text |Cite
|
Sign up to set email alerts
|

BRAF Mutation Is Rare in Advanced-Stage Low-Grade Ovarian Serous Carcinomas

Abstract: Low-grade ovarian serous carcinomas are believed to arise via an adenoma-serous borderline tumor-serous carcinoma sequence. In this study , we found that advanced-stage , low-grade ovarian serous carcinomas both with and without adjacent serous borderline tumor shared similar regions of loss of heterozygosity. We then analyzed 91 ovarian tumor samples for mutations in TP53, BRAF , and KRAS. TP53 mutations were not detected in any serous borderline tumors (n ‫؍‬ 30) or low-grade serous carcinomas (n ‫؍‬ 43) but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
151
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(167 citation statements)
references
References 43 publications
15
151
1
Order By: Relevance
“…4 Although some reports have shown BRAF mutations in about 30% of cases, 4,30 our inability to detect BRAF V600E mutation in a single low-grade serous carcinomas is in line with a previous report in which Wong et al 31 assessed 43 advanced stage low-grade serous carcinomas. KRAS mutations were detected in 19% of cases, whereas BRAF mutations were found in only 2% of cases, which is very similar to our results.…”
Section: Discussionsupporting
confidence: 88%
“…4 Although some reports have shown BRAF mutations in about 30% of cases, 4,30 our inability to detect BRAF V600E mutation in a single low-grade serous carcinomas is in line with a previous report in which Wong et al 31 assessed 43 advanced stage low-grade serous carcinomas. KRAS mutations were detected in 19% of cases, whereas BRAF mutations were found in only 2% of cases, which is very similar to our results.…”
Section: Discussionsupporting
confidence: 88%
“…34). Although the incidence of BRAF mutations appears lower in recent reports (35), the Ras/MEK/ERK pathway is still an attractive therapeutic target in this notoriously difficult disease. A phase II trial of the MEK1/2 inhibitor selumetinib (AZD6244) in 52 patients with recurrent LGSOC has shown promising results (36): The overall response rate was 15.4%, disease stabilization 65%, and median PFS 11 months.…”
Section: Ras/raf/mek/erk Pathwaymentioning
confidence: 99%
“…Most studies of ovarian LGSC reported a low frequency of BRAF mutations (Table 4). 11,27,45,[55][56][57][58][59] In one study of the implants that accompany ovarian SBTs, only six (13%) of 45 patients had BRAF mutations in SBTs with noninvasive peritoneal implants, and none of the patients had BRAF mutations in SBTs with invasive implants. 43 Heublein et al 44 detected BRAF mutations in only noninvasive implants associated with ovarian SBTs.…”
Section: Role Of Braf Mutation In the Pathogenesis Of Ovarian Cancermentioning
confidence: 99%
“…Validation of BRAF mutations as a potential prognostic marker in a large cohort of patients with ovarian SBTs or LGSC is necessary to determine the clinical significance of BRAF status in the management of patients with this disease. Once the BRAF mutation has been confirmed as a protective factor against the progression of ovarian SBTs and early-stage LGSC into more aggressive disease, 11,23,43,58 clinicians will be able to use the BRAF status of surgically resected ovarian SBTs to predict the risk of recurrence. Moreover, for progressive SBT/LGSC with BRAF V600E mutation, treatment with BRAF V600E specific inhibitor could be an alternative regimen.…”
Section: Future Perspectivesmentioning
confidence: 99%